Tratamento precoce com o trans-4-metoxi-beta-nitroestireno previne o desenvolvimento da hipertensão arterial pulmonar induzida por monocrotalina em ratos - Silva, Jussara Matyelle Rodrigues da (2020)
Pulmonary arterial hypertension (PAH) is a severe and progressive disease of the small pulmonary arteries. In this context, the aim of this study was to study the preventive effect of trans-4-methoxy-beta-nitrostyrene (T4MN), a substance that stimulates the nitric oxide / guanylate cyclase soluble / cyclic guanosine monophosphate pathway (NO / sGC/ GMPc), in the experimental model of PAH in rats. For that, Wistar rats were used that received subcutaneous injection of 60 mg / kg of monocrotaline (MCT) on day zero (D0). After 1h, treatment by gavage route with T4MN at doses of 18.75 and 37.5 mg/kg and mg / kg was started. After the treatment period for 28 consecutive days, the experiments were carried out. Treatment with T4MN was unable to improve some rates of cardiac hypertrophy. However, treatment with this nitroderivative caused a significant improvement of pulmonary hypertrophy. The results from hemodynamic studies showed that T4MN significantly reduces right ventricular systolic pressure (RVSP) in PAH and improves endothelium-dependent vascular relaxation, in addition to reducing the vasoconstrictor effect induced by phenylephrine, an alpha1-adrenergic agent. Therefore, in the experimental conditions of the present study, T4MN exhibited potential activity in the early treatment of pulmonary arterial hypertension.